The effects of Fraxini cortex and Andrographis herba on Escherichia coli-induced diarrhea in chicken - Yunying Wang; Zhenwei Sheng; Huicong Li; Xuewen Tan; Yingqiu Liu; Weimin Zhang; Wuren Ma; Lin Ma; Yunpeng Fan (Poultry Science)
Escherichia coli (E. coli) is a type of pathogenic bacteria that often causes diarrhea in poultry. While antibiotics can control E. coli-induced diarrhea in chickens, it can lead the ongoing proliferation of antibiotic resistance. Traditional Chinese medicines (TCMs) that effectively protect against and treat chicken diarrhea caused by E. coli are an encouraging alternative. That enhance poultry immunity, curtail antibiotic resistance, and provide a secure, eco-friendly, and efficacious option for the livestock and poultry industry. In this study, the model of chicken diarrhea induced by E. coli was established, and different TCM formulas were used for treatment, and finally the formula with the best effect was screened out. The research also investigated the impact of these formulas on gut microbiota and serum metabolites in chickens, using 16S rRNA sequencing technology and metabolomics. Mass spectrometry technology and network pharmacology were used to analyze the optimal TCM formula corroborated by molecular docking and qPCR for further explore mechanism exploration. The findings indicated that Fraxini cortex and Andrographis herba dramatically lowered mortality rates and alleviated pathologic changes in cases of avian E. coli diarrhea (P < 0.05). Fraxini cortex and Andrographis herba significantly boosted the abundance of Bacteroidetes (P < 0.05) and mainly enhanced cysteine and methionine metabolic pathways. Moreover, 97 active ingredients in Fraxini cortex and Andrographis herba were identified, along with 1425 diarrhea-related targets, primarily enriched in the MAPK signaling pathway. Molecular docking and qPCR revealed that the crucial active ingredients in Fraxini cortex and Andrographis herba bonded effectively with disease targets and treated diarrhea by regulating the MAPK signaling pathway. This suggests that Fraxini cortex and Andrographis herba exerts an optimal effect on diarrhea by multi-target and multi-pathway regulation of metabolic pathways and gut microbiota.